DECODING SOCIO-COGNITIVE ELEMENTS IN INDONESIAN ONLINE NEWS: A SYSTEMIC FUNCTIONAL MULTIMODAL DISCOURSE ANALYSIS - Lucky Rahayu Nurjamin; Dadang Sudana; Wawan Gunawan (English Review: Journal of English Education, 2023)
This study explores the representation of socio-cognitive components in Indonesian political multimodal news text using the framework of Systemic Functional Multimodal Discourse Analysis (SF-MDA). With the increasing prominence of multimedia in contemporary news production, understanding how socio-cognitive aspects are conveyed through multiple modes becomes essential. Drawing on SF-MDA, which combines systemic functional linguistics and multimodal analysis, the study examines how Indonesian political news texts incorporate social and cognitive elements to shape meaning and influence audience perceptions. This study was undertaken qualitatively involving three online news published by Indonesia’s publishers as the data. The result reveals that the visual and verbal modes merged in the news tend to highlight the good image of the political figures. It means that the meanings of visual and verbal components of the news persuasively work together to create the good impressions among readers to the human actor in the news. As the implication, multimodal resources are strategically employed to shape public opinion and promote specific political ideologies. Ultimately, this research aims to contribute to the development of critical media literacy and foster a more nuanced understanding of the socio-political dynamics in contemporary Indonesia.